Ethnic cultural representation in digital media: motivations of short video creators from minority groups - Li, Li; Mohammad Razi, Siti Aishah; Yaakup, Hani Salwah (Redfame Publishing, 2025)
Based on the classic theory of communication, the uses and gratifications theory, this study takes the Naxi ethnic group of southwestern China as an example to explore the motivational mechanism of ethnic minority groups participating in short video creation. A combination of purposive sampling and snowball sampling was adopted to select 16 Naxi short video creators as the research subjects. Semi-structured interviews and the scroll back method were innovatively used to collect textual and visual data from the interviews, and in-depth analysis was conducted using textual-visual thematic analysis. The study found five main creative motivations: cultural dissemination and inheritance; coping with misunderstanding and marginalization; seeking expression and belonging; career development and economic incentives; and interests and entertainment. The results reveals a paradoxical dynamic: while digital media empowers cultural expression, it also creates pressures that can lead to digital inequality and cultural homogenization.